Usefulness of preoperative point-of-care ultrasound measurement of the lateral parapharyngeal wall to predict difficulty in mask ventilation. Issue 5 (15th September 2022) - Mehta, Nikita; Lee, Esther; Pence, Madeline; Nice, Wyatt; Keneally, Ryan; Pla, Raymond; Vincent, Anita; Heinz, Eric
Abstract: Measurement of the lateral parapharyngeal wall has been shown to correlate with severity of obstructive sleep apnea, which is believed to increase risk of difficulty in mask ventilation (MV). This study aimed to assess the efficacy of using ultrasound to measure the lateral parapharyngeal wall thickness (LPWT) to predict the difficulty of MV. The LPWT was measured as the distance between the inferior border of the carotid artery and the lateral wall of the pharynx. Difficulty of MV was assessed according to an MV scale. A total of 92 patients were enrolled. Measurements of the LPWT ranged from 1.52 to 4.43 cm. There was a significant correlation between LPWT and difficulty of MV ( P = 0.004). Every increase in 1 cm of LPWT was associated with an odds of increase in MV score of 3.17 ( P < 0.05). With a cutoff of 3.5 cm, the area under the curve for LPWT was 0.67. The negative predictive value was 0.89, and the positive predictive value was 0.57. Use of point-of-care ultrasound to measure the LPWT shows promise in its ability to aid in airway management planning. Ultrasonic measurements of the LPWT have reasonable accuracy for predicting difficulty of MV.